Permasalahan LGBT di kawasan pondok pesantren: Studi kasus gay pada mahasiswa alumni pondok pesantren - Fadllik, Fina Rif’atu (Maliki Interdisciplinary Journal, 2024)
LGBT stands for Lesbian, Gay, Bisexual, and Transgender. This LGBT problem has been going on for decades. Until now, this problem has caused a lot of unrest for the surrounding community. Sometimes, someone who experiences a case like this does not see the situation and condition. Many of them carry out these activities in a blatant way without any discomfort or shame towards others. One of the problems that often arises is the case of Gay. This is a sign of the poor morality of today is life. The purpose of this study is to find out what factors influence a student who is an alumnus of an Islamic boarding school to commit the Gay act. This research , which is a type of case study research to someone directly. The data collection technique used in this study was an interview by giving several questions and wanting to find out what caused the factors of commiting Gay actions to the source to answer honestly according to what he had experienced. The object of this research was a student who used to be a student of the Islamic boarding school who had experienced a Gay case during his education at the Islamic boarding school. The results showed that there were several factors that influenced the Gay problem of a student alumnus of Islamic boarding schools. These factors include : Self- desire, environment, family, and also friend factors.